ANALYSIS OF ORGANIZING THE DELIVERY OF HUMANITARIAN AID IN CRISIS SITUATIONS - Nesterenko, H. I.; Muzykin, M. I.; Bibik, S. I.; Strelko, O. H.; Aleksieieva, A. O. (Systems and Technologies, 2024)
The article is devoted to analyzing humanitarian logistics in Ukraine, which has developed significantly since 2014 and increased, in particular, during the full-scale invasion of 2022. Humanitarian logistics have become critical to supporting both the military and civilians affected by the conflict. The authors research the impact of various aspects of humanitarian aid, including economic factors such as reduced exports and a drop in the gross domestic product (GDP), on the volume and efficiency of humanitarian aid delivery. In particular, the impact of the closure of large metallurgical enterprises on the country’s economy is analyzed. The activities of such charitable organizations as “Come Back Alive” and “Volunteering and Help Center” were reviewed, which carry out mass transportation of humanitarian goods and provide support to both military and civilian persons. These organizations play a key role in providing the population with necessary resources, such as medicine, food, hygiene products, clothing, etc. They also actively collaborate with international partners and volunteer groups to coordinate aid and improve logistics processes. Data on the amount of support provided by category (hygiene, medicine, food, etc.) are also considered. The article provides an analysis of the logistics routes used for the delivery of goods, taking into account various factors such as the safety of the routes, the efficiency of the transportation process, and the speed of delivery. The importance of flexibility and adaptability of logistics systems in the conditions of continued martial law is highlighted. The research emphasizes the importance of cluster analysis and clustering methodologies for effective decision-making in the field of humanitarian logistics. The article also includes references to legislative acts and portals that regulate and support humanitarian aid in Ukraine. These resources provide a legal basis for the activities of charities and provide important information for donors and volunteers. They contribute to the transparency and accountability of the aid delivery process, which is critical for maintaining trust on the part of the international community and the population of Ukraine.